Pengaruh Kesehatan Dan Keselamatan Kerja (K3) Dan Jenjang Karir Terhadap Kepuasan Kerja Karyawan Pada PT. PLN (PERSERO) Ulp Bintuhan - Aan Hendri Saputra; Karona Cahya Susena; Nurzam Nurzam (Fakultas Ekonomi Universitas Dehasen Bengkulu, 2023)
The purpose of this study were: to determine the effect of occupational safety and health (K3) on employee job satisfaction at PT. PLN (Persero) ULP Bintuhan; to determine the effect of career level on employee job satisfaction at PT. PLN (Persero) ULP Bintuhan and to determine the effect of occupational safety and health (K3) and career level on employee job satisfaction at PT. PLN (Persero) ULP Bintuhan. The analytical method used is validity test, reliability test, simple linear regression, coefficient of determination, F test and t test.Based on the research results indicate that occupational safety and health or K3 (X1) partially has a significant effect on job satisfaction of employees of PT. PLN (Persero) ULP Bintuhan (Y) because the significant value is 0.000 < 0.05. Career level (X2) partially has a significant effect on job satisfaction of employees of PT. PLN (Persero) ULP Bintuhan (Y) because the significant value is 0.000 < 0.05. Occupational safety and health variables or K3 (X1), career level (X2) simultaneously or together have a significant effect on employee job satisfaction (Y) at PT. PLN (Persero) ULP Bintuhan because the significant value is 0.000 < 0.05